The frequency of differentiated CD3+CD27-CD28- T cells predicts response to CART cell therapy in diffuse large B-cell lymphoma - Worel, Nina; Grabmeier-Pfistershammer, Katharina; Kratzer, Bernhard; Schlager, Martina; Tanzmann, Andreas; Rottal, Arno; Körmöczi, Ulrike; Porpaczy, Edit; Staber, Philipp B.; Skrabs, Cathrin; Herkner, Harald; Gudipati, Venugopal; et al. (Frontiers in Immunology, 2023)
Background: Chimeric antigen receptor T (CART) cell therapy targeting the B cell specific differentiation antigen CD19 has shown clinical efficacy in a subset of relapsed/refractory (r/r) diffuse large B cell lymphoma (DLBCL) patients. Despite this heterogeneous response, blood pre-infusion biomarkers predicting responsiveness to CART cell therapy are currently understudied. Methods: Blood cell and serum markers, along with clinical data of DLBCL patients who were scheduled for CART cell therapy were evaluated to search for biomarkers predicting CART cell responsiveness. Findings: Compared to healthy controls (n=24), DLBCL patients (n=33) showed significant lymphopenia, due to low CD3+CD4+ T helper and CD3-CD56+ NK cell counts, while cytotoxic CD3+CD8+ T cell counts were similar. Although lymphopenic, DLBCL patients had significantly more activated HLA-DR+ (P=0.005) blood T cells and a higher frequency of differentiated CD3+CD27-CD28- (28.7±19.0% versus 6.6±5.8%; P<0.001) T cells. Twenty-six patients were infused with CART cells (median 81 days after leukapheresis) and were analyzed for the overall response (OR) 3 months later. Univariate and multivariate regression analyses showed that low levels of differentiated CD3+CD27-CD28- T cells (23.3±19.3% versus 35.1±18.0%) were independently associated with OR. This association was even more pronounced when patients were stratified for complete remission (CR versus non-CR: 13.7±11.7% versus 37.7±17.4%, P=0.001). A cut-off value of ≤ 18% of CD3+CD27-CD28- T cells predicted CR at 12 months with high accuracy (P<0.001). In vitro, CD3+CD8+CD27-CD28- compared to CD3+CD8+CD27+CD28+ CART cells displayed similar CD19+ target cell-specific cytotoxicity, but were hypoproliferative and produced less cytotoxic cytokines (IFN-g and TNF-a). CD3+CD8+ T cells outperformed CD3+CD4+ T cells 3- to 6-fold in terms of their ability to kill CD19+ target cells. Interpretation: Low frequency of differentiated CD3+CD27-CD28- T cells at leukapheresis represents a novel pre-infusion blood biomarker predicting a favorable response to CART cell treatment in r/r DLBCL patients. Funding: Innovative Medicines Initiative (IMI) T2EVOLVE agreement No 945393; European Union’s Horizon 2020 research and innovation program and EFPIA.